A Red boyhood growing up under Stalin - Konstantin, Anatole, 1928- (University of Missouri Press, 2008)
"A childhood memoir of Stalin's Soviet Union that details the daily trials of people trapped in this regime. Left fatherless by Stalin's purges, then forced to flee the Germans and live as an impoverished refugee in Kazakhstan during World War II, Konstantin eventually escapes to Western Europe at war's end"--Provided by publisher.